2021
DOI: 10.1161/circulationaha.121.054071
|View full text |Cite
|
Sign up to set email alerts
|

Role of Venous Endothelial Cells in Developmental and Pathologic Angiogenesis

Abstract: Background: Angiogenesis is a dynamic process that involves expansion of a pre-existing vascular network that can occur in a number of physiologic and pathologic settings. Despite its importance, the origin of the new angiogenic vasculature is poorly defined. In particular, the primary subtype of endothelial cells (capillary, venous, arterial) driving this process remains undefined. Methods: Endothelial cells were fate-mapped using genetic markers speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 44 publications
4
89
0
Order By: Relevance
“…After ischemic stroke, if the formation of new blood vessels in the ischemic penumbra is promoted, blood reperfusion can be increased, which is beneficial to reducing the volume of cerebral infarction, neuronal remodeling, prolonging survival times, and functional recovery [ 111 , 112 ]. Angiogenesis is a dynamic process that is induced by the sprouting of endothelial cells (ECs) from pre-existing vessels, thus expanding the pre-existing vascular network [ 113 ]. Under a number of physiological and pathological conditions, the endothelial cells degrade the basement membrane, migrate to adjacent tissues, proliferate, and aggregate into tubular shape, thereby forming new blood vessels.…”
Section: Ccl2/ccr2 Axis and Cerebral Ischemia-reperfusion Injury And ...mentioning
confidence: 99%
“…After ischemic stroke, if the formation of new blood vessels in the ischemic penumbra is promoted, blood reperfusion can be increased, which is beneficial to reducing the volume of cerebral infarction, neuronal remodeling, prolonging survival times, and functional recovery [ 111 , 112 ]. Angiogenesis is a dynamic process that is induced by the sprouting of endothelial cells (ECs) from pre-existing vessels, thus expanding the pre-existing vascular network [ 113 ]. Under a number of physiological and pathological conditions, the endothelial cells degrade the basement membrane, migrate to adjacent tissues, proliferate, and aggregate into tubular shape, thereby forming new blood vessels.…”
Section: Ccl2/ccr2 Axis and Cerebral Ischemia-reperfusion Injury And ...mentioning
confidence: 99%
“…Because endothelial cells in the capillary bed are embedded in thinner basement membranes than those in arteries and veins 36 , 37 , it has been hypothesized that capillary endothelial cells are the source of endothelial expansion. However, this idea has been challenged by recent findings that venous endothelial cells are the primary source of endothelial cells for angiogenic expansion during developmental and pathological angiogenesis 8 .…”
Section: Traditional Angiogenesis Modelmentioning
confidence: 99%
“…A recent study 8 reported that venous endothelial cells are the primary source of endothelial cells responsible for angiogenic expansion both during embryonic development and in disease settings. Remarkably, venous endothelial cells are the only type of endothelial subtype capable of responding to hypoxia-induced angiogenic signaling by proliferating and migrating against the blood flow to form the new vascular bed.…”
Section: Introductionmentioning
confidence: 99%
“…4i, g and SM 4). About half of the overlapped genes have been found to be related to PD in previous studies, and the rest genes are related to neuropsychiatric diseases (Zbtb20, Nav3), tissue aging (Myof), impaired memory (Atp10a), blood-brain barrier (Slco1a4/5, Cldn5, Ly6a) [44][45][46] .…”
Section: Trajectory Reconstruction Of Mtpt-pd Associated Astrocytes A...mentioning
confidence: 99%